Design of an Archiving Information System using the Agile Scrum Method - Setiawan, Denny Farissa; Rahardja, Yani (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
This study aims to design and implement a web-based archiving information system at PT Sarana Tirta Ungaran using the Agile Scrum methodology. The background of this research lies in the challenges of manual archive management, which often lead to difficulties in document retrieval, risks of data loss, and inefficient use of storage space. By adopting the Agile approach, the system was developed iteratively through stages such as product backlog, sprint planning, and daily Scrum, allowing for dynamic adjustments to user requirements. The system incorporates four types of user roles—super admin, admin, director, and general administrative staff—with key features including login, archive management (CRUD), document search, and activity logs. The design process employed UML, covering use case diagrams, activity diagrams, and class diagrams. Testing results demonstrate that the system improves archiving efficiency, accelerates information access, and supports the digitalization process within the company. Therefore, this information system is expected to enhance overall organizational performance.